If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -5x = 6(x + 2) Reorder the terms: 12 + -5x = 6(2 + x) 12 + -5x = (2 * 6 + x * 6) 12 + -5x = (12 + 6x) Add '-12' to each side of the equation. 12 + -12 + -5x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 0 + -5x = 12 + -12 + 6x -5x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 -5x = 0 + 6x -5x = 6x Solving -5x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5x + -6x = 6x + -6x Combine like terms: -5x + -6x = -11x -11x = 6x + -6x Combine like terms: 6x + -6x = 0 -11x = 0 Divide each side by '-11'. x = 0 Simplifying x = 0
| 3.4k=7.82 | | 2q-5=11 | | 225x^2-121y^2= | | 7+-3=18 | | 1-100x^2= | | (2c-1)=3c-2 | | 10+5(z-2)=-3z+3 | | 2x^3+3x^2-120=f(x) | | 3/4*3/4= | | -52=5x-4(-x-5) | | 2x^3+3x^2-120=0 | | 10-6x-3=1 | | 24(x+3)=0 | | 28-z=5 | | 2+14a=20a-5a | | z*z-(2+1i)z+(-1+7i)=0 | | -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) | | -5x=2x | | x^2-12x=8064 | | 8(5k-3)=-264 | | x^2-12x=5440 | | 9(y+5)=8y-6 | | 125*.38= | | -2x+2(-4x-3)=74 |